Cleaner fish Labroides dimidiatus manipulate client reef fish by providing tactile stimulation - Bshary, Redouan; Wurth, Manuela (My University, 2001)
The cleaner wrasse Labroides dimidiatus often touches 'client' reef fish dorsal fin areas with its pelvic and pectoral fins. The relative spatial positions of cleaner and client remain constant and the cleaner's head points away from the client's body. Therefore, this behaviour is not compatible with foraging and the removal of client ectoparasites. As clients seek such 'tactile stimulation', it can be classified as an interspecific socio-positive behaviour. Our field observations on 12 cleaners (observation time of 112 h) suggest that cleaners use tactile stimulation in order to successfully (i) alter client decisions over how long to stay for an inspection, and (ii) stop clients from fleeing or aggressive chasing of the cleaner in response to a cleaner fish bite that made them jolt. Finally predatory clients receive tactile stimulation more often than non-predatory clients, which might be interpreted as an extra service that cleaners give to specific partners as pre-conflict management, as these partners would be particularly dangerous if they started a conflict. We therefore propose that cleaner fish use interspecific social strategies, which have so far been reported only from mammals, particularly primates.
Keywords: Labroides dimidiatus; mutualism; cooperation; exploitation; reconciliation; LONG-TAILED MACAQUES; RECONCILIATION; LABRIDAE; WRASSE; RATES